Higher Education Teaching Practices Experience in Mexico, During the Emergency Remote Teaching Implementation due to COVID-19 - Zapata-Garibay, Rogelio; González-Fagoaga, Jesús Eduardo; González-Fagoaga, Clara Judith; Cauich-García, José Rafael; Plascencia-López, Ismael (Frontiers in Education, 2021)
Higher education teaching practices experience in Mexico changed from face-to-face teaching to the emergency remote teaching derived from the health contingency by COVID-19. The change from face-to-face to an online modality in the Mexican education system represented a great challenge for teachers of all educational levels. In Mexico, the federal government declared on Tuesday, March 24, 2020, Phase 2 of the plan to address the country's Covid 19 pandemic. Governments in at least ten states decided to suspend their activities and services as of March 17, including the education system. On April 13, the Mexican education system began activities in the online modality exclusively; however, derived from the country's technical adequacy and digital connectivity conditions, a large proportion of the educational campuses, academic programs, and the teaching staff were not prepared for this situation. This cross-sectional study was carried out to analyze the faculty members' experiences about the change from face-to-face to an online modality in the health emergency context due to the COVID-19 outbreak. We designed a study to gather information on practice in the new online learning scenario. For this purpose, we collected data on the previous experience in the conduct of online courses, the technological tools used, the barriers faced while driving online courses, the current conditions of use of educational and technological tools, the vision for the future, and some indicators of physical and mental health. In a sample of 341 faculty members, those working in public institutions were on less favorable terms than their peers attached to private universities. In contrast, lecturers recorded better conditions for dealing with modality change than full-time teachers. Likewise, lecturers more often mentioned having their infrastructure to teach courses from their homes than full-time teachers, which indeed responds to less access to the universities' facilities in which they teach. Another important aspect to highlight is the increased proportion of teachers in public institutions and lecturers who have other jobs, so their workload can be more intense than those of their peers.